La classe de langue à l’ère du digital. Quelques réflexions sur l’intégration des compétences numériques en didactique des langues étrangères - Gałan, Beata (Neofilolog, 2021)
Digital skills are an important part of the skills required in the 21st century, enabling users to better utilise information and communication technologies (ICT) in different spheres of life. This article examines the integration of these skills into foreign language teaching. The first part of the article studies the notion of digital skills through initiatives undertaken at the European and the national level as well as the current role of digital technology in the language classroom. The second part of the article focuses on the possible integration of digital skills with the development of productive language skills through active methods (collaborative learning, project-based learning, problem-based learning). The preliminary examination shows that the use of these teaching strategies could possibly ensure the parallel development of language and digital skill.